Process analysis and simulation in chemical engineering. (2015) - Chaves, Iván Dario Gil; Lopez, Javier Ricardo Guevara; García Zapata, José Luis; Robayo, Alexander Leguizamón; Niõ, Gerardo Rodríguez
No abstract available